Electrocatalytic degradation of reactive blue 49 on Pt, Au, and carbon felt: Influence of operating parameters - Fatima Zaaboul; Ghizlan Kaichouh; Abdelaali Balahbib; Khang Wen Goh; Abdelhakim Bouyahya; Abderrahim El Hourch (Results in Chemistry, 2025)
The problem of pollution of surface water by dyes discharged by various industries is a serious environmental issue. However, electrochemical oxidation is emerging as a promising alternative for water treatment. In this work, we focus on the electrochemical oxidation of the dye RB49, evaluating the efficiency of FC, gold and Pt anodes. To study the electrocatalytic activity of FC, gold and Pt materials, we used the electrocatalytic oxidation of the azo dye Reactive Blue 49 (RB49). Cyclic voltammetry (CV) tests were also carried out to study the electrochemical response of these electrodes in acidic and basic environments. We studied the impact of various parameters such as pH, supporting electrolyte and current density. We assessed the efficiency of the electrocatalytic oxidation process using UV–visible spectrometry and chemical oxygen demand (COD). In general, the results obtained show that the FC, Gold and Pt electrodes perform well in terms of RB49 degradation. However, the results indicate that the carbon felt (FC) electrode exhibits superior performance in the degradation of Reactive Blue 49 (RB49) compared to the gold and platinum electrodes.